Communication disabilities sourcebook - 4 0 16; 1963- Williams, Angela; 5 (Detroit, MI : Omnigraphics, 2020)
Provides basic health information about different types of communication disorders and their impact on personal, social, and economic well-being, recovery and rehabilitation techniques, tips for caregivers, and rights and benefits of people with communication disabilities. Includes a directory of organizations for additional help and information--
What is voice? What is speech? What is language? -- Speech and language developmental milestones -- Communication variations -- What is communication disorder? -- Hearing disorder -- Deaf and hard of hearing -- Language disorder -- Apraxia of speech -- Speech disorder -- Autism spectrum disorder -- Statistics about people with voice, speech, and language disorders -- Communication disorders in children -- How does a communication disability affect a person's life? -- The impact of a communication disorder on family and interpersonal relationships -- Cultural attitudes toward communication disabilities and stigma -- Media portrayal of communication disabilities -- Should you disclose your communication disability to your employer? -- Employment options for people with a communication disorder -- Recovery models -- Speech-language pathologists -- Peer support and recovery -- Guiding principles of recovery -- Healthy lifestyle to support recovery -- Supported employment for people with a communication disorder -- Rehabilitation medicine -- Health and well-being -- Caregiving : tips for caring for a person with a communication disorder -- Technology and the future of treatment for a communication disorder -- Americans with disabilities act -- Rights of students with a disability -- Accommodations for employees with a disability -- Impact in the workplace -- Legal requirements to qualify for social security disability benefits -- Disability rights movement -- Neurodiversity movement -- Organizations that provide services for people with communication disorders.
Description based on print version record and CIP data provided by publisher; resource not viewed.
Keywords: 2 -- 0; 6; Communicative disorders.;People with communicative disabilities. -- 20; 20; 2